FACTORS INFLUENCING THE FORMATION OF AHMAD DONISH’S PHILOSOPHICAL VIEWS AND THE HISTORICAL CONDITIONS OF HIS CREATIVE WORK - Miltiqboyev Bobur Zokirovich (Sciental Journals Publishing, 2025)
This article examines the historical conditions of Ahmad Donish’s creative activity and the key factors that influenced the formation of his philosophical views. The study highlights the socio-political, cultural, and educational environment of the 19th century, which shaped Donish’s intellectual outlook and reformist ideas. Special attention is given to the role of Eastern philosophical traditions, enlightenment values, and national identity in the development of his worldview. The research emphasizes that Ahmad Donish’s legacy reflects a synthesis of progressive thought, moral responsibility, and social reform, which remain significant in the context of modern intellectual history.